High resolution investigation of pH on control of mobile and organic phosphorus and associated release kinetics following lanthanum modified bentonite (LMB) amendment at the water-sediment interface. (1st May 2021) - Kong, Ming; Liu, Feifei; Zhang, Wenjing; Xu, Xueting; Chao, Jianying; Wang, Peifang; Wang, Chao; Gao, Yuexiang
Abstract: Herein, we discuss the impact of water pH on mobile and organic phosphorous (P), as well as the kinetics and efficacy of P responses following LMB amendment at the sediment-water interface. For this study, we conducted a microcosm incubation experiment over a 90-day period during which the pH of the overlying water was continuously adjusted. Over the course of this experimental period, one- and two-dimensional soluble and labile P sediment profiles were assessed using high-resolution Peeper (HR-Peeper) and diffusive gradients in thin-film (DGT) probes. These analyses revealed that rising water column pH can induce significant increases in SRP and labile P concentrations, as well as substantial changes in levels of inorganic P (IP) and organic P (OP) species. The P release kinetics under different pH conditions were calculated using a DGT-induced flux in sediments (DIFS) model. We found that sediment still serves as a P pool following LMB addition, ultimately resupplying soluble P to the overlying water. However, P release became increasingly challenging with reduction in pH. Together, our results provided direct evidence regarding the impact of pH on efficiency of the LMB capping of phosphorous, potentially guiding future studies of the engineering application of LMB.